2016
DOI: 10.1177/1461355716677876
|View full text |Cite
|
Sign up to set email alerts
|

Nudging down theft from insecure vehicles. A pilot study

Abstract: This report presents the preliminary findings of a pilot study to reduce thefts from cars committed against insecure vehicles, using the behavioural insights or ‘nudge approach’. The recipients of the ‘nudges’ were potential victims of theft from insecure vehicles living in high rate areas for this crime, where a bespoke leaflet campaign was developed to nudge vehicle owners into thinking more carefully when leaving their vehicles unattended, particularly when left on their driveways overnight. Although somewh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…However, for the former two reasons the police may wish to employ campaigns to increase their followers as the reasons attested in the present study would suggest the police may simply increase their followers by advertising the importance of their social media accounts. Furthermore, employing NUDGE psychology approaches that have been increasingly adopted and proven to be useful in policing contexts (Roach et al , 2016; Roach et al , 2019) might be a useful methodology for increasing social media followers. After all, by increasing the audience associated with police social media accounts allows for greater effectiveness in relation to the second objective of police social media use (Lee and McGovern, 2013) by communicating operational messages to a larger range of the community.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the former two reasons the police may wish to employ campaigns to increase their followers as the reasons attested in the present study would suggest the police may simply increase their followers by advertising the importance of their social media accounts. Furthermore, employing NUDGE psychology approaches that have been increasingly adopted and proven to be useful in policing contexts (Roach et al , 2016; Roach et al , 2019) might be a useful methodology for increasing social media followers. After all, by increasing the audience associated with police social media accounts allows for greater effectiveness in relation to the second objective of police social media use (Lee and McGovern, 2013) by communicating operational messages to a larger range of the community.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent vehicle theft in Durham in the United Kingdom, Roach et al (2017) developed a leaflet campaign to nudge vehicle owners into locking their vehicle when leaving it unattended. Results showed that the number of thefts committed against insecure vehicles in the treatment areas was reduced significantly in comparison with the control areas where no nudges were implemented.…”
Section: Nudges In the Field Of Securitymentioning
confidence: 99%
“…In their pilot study attempting to reduce vehicle theft, Roach et al used leaflets, a nominal SCP approach, to "nudge" victims into securing their vehicles. 73 The "nudge" was not the presence of the leaflet itself, but their content, which intuitively encouraged recipients to make better choices. Despite their theoretical differences (such as "nudge" preserving the "freedom to offend" while SCP often aiming to physically prevent it), this example shows that the two theories can (and perhaps should more often) complement each other.…”
Section: Devising Community-led Preventative Approachesmentioning
confidence: 99%